Rantai Pasok Kopra Di Desa Pakuure Tiga Kecamatan Tenga Kabupaten Minahasa Selatan (Copra Supply Chain in Pakuure Tiga Village, Tenga District, South Minahasa Regency) - Potu, Gabriela Aprilia Anggreini; Pakasi, Caroline Betsi Diana; Rori, Yolanda Pinky Ivanna (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to determine the copra supply chain in Pakuure Tiga Village, Tenga District, South Minahasa Regency. This research was conducted from September to November 2022. Data collection in this study used two types of data, namely primary data and secondary data. The sampling method in this study used two stages, namely the first stage of determining the sample population of farmers using purposive sampling method and the second stage of determining the sample of collectors using the snowball sampling method. Data analysis used in this research is descriptive analysis. The results showed that the copra supply chain stakeholders in Pakuure Tiga Village consisted of Farmers - Collectors - PT. Cargil Indonesia Contractors - Factories. The product flow starts with coconut farmers producing copra, then selling the copra to the collecting traders and then the collecting traders distributing the copra to the contractor PT. Cargil Indonesia then goes to the factory to be processed. The financial flow that starts from the factory buys copra to the collectors then the collectors buys the copra from the farmers. The flow of information flows from two directions where the first direction is PT. Cargil Indonesia to contractors, then to collectors, then collectors to farmers. The direction of the two farmers is to the collectors then the collectors inform the factory.